Neurogenic bladder: Highly selective rhizotomy of specific dorsal rootlets maybe a better choice. (February 2016) - Zhu, Genying; Zhou, Mouwang; Wang, Wenting; Zeng, Fanshuo
Abstract: Spinal cord injury results not only in motor and sensory dysfunctions, but also in loss of normal urinary bladder functions. A number of clinical studies were focused on the strategies for improvement of functions of the bladder. Completely dorsal root rhizotomy or selective specific S2-4 dorsal root rhizotomy suppress autonomic hyper-reflexia but have the same defects: it could cause detrusor and sphincter over-relaxation and loss of reflexive erection in males. So precise operation needs to be considered. We designed an experimental trail to test the possibility on the basis of previous study. We found that different dorsal rootlets which conduct impulses from the detrusor or sphincter can be distinguished by electro-stimulation in SD rats. Highly selective rhizotomy of specific dorsal rootlets could change the intravesical pressure and urethral perfusion pressure respectively. We hypothese that for neurogenic bladder following spinal cord injury, highly selective rhizotomy of specific dorsal rootlets maybe improve the bladder capacity and the detrusor sphincter dyssynergia, and at the same time, the function of other pelvic organ could be maximize retainment.